Case Report: An Unusual Case of Ectopic ACTH Syndrome Caused by Mediastinal Paraganglioma - Li, Bo; Yan, Zhe; Huang, Hui (Frontiers in Endocrinology, 2022)
Ectopic adrenocorticotrophic hormone (ACTH) syndrome is not common, which is more unusual when caused by paraganglioma. We herein present a 40-year-old Chinese male who was diagnosed with ACTH-dependent Cushing’s syndrome. However, the localization of the ACTH source was troublesome due to the inconsistent results of the high-dose dexamethasone suppression test and the desmopressin stimulation test. Bilateral inferior petrosal sinus sampling was performed, and ectopic ACTH syndrome was diagnosed. After 68Ga-DOTATATE-PET/CT and 18F-FDG-PET/CT were performed, it was localized in the anterior mediastinum. Post-operation histopathology demonstrated an ACTH-secreting mediastinal paraganglioma. The patient obtained complete clinical remission after a mediastinal tumorectomy.